PENERAPAN MODEL DISCOVERY LEARNING DAN ASESMEN AUTENTIK UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA PADA MATA PELAJARAN BIOLOGI KELAS X.1 AK SMK FARMASI IKASARI PEKANBARU TAHUN PELAJARAN 2015/2016 - Trisa Novia Sari; Mariani Natalina Linggasari; Irda Sayuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : this study is a class action research which was conducted in twocycles, the subject of this study was 39 tenth grade students in X.1AK SMK FarmasiIkasari Pekanbaru academic year 2015/2016, it aimed to increasestudent science skillprocess by applied model discovery learning and assessment authentic.Researchprocedureconsist of plan, action and observation, and reflection. Data was collected inthis research was science skill process in three domain those were cognitive, affectiveand psychomotor.The data was collected using test and observation. In addition to dataof science process skills , there are also the result of the application of authenticassessment that the reference assessment intact in the application of this model . Theresults showed that each domain process skills increased.Science skill process incognitive aspect that was seen from test result in cycle I was 82 (enough) and increasein cycle II, that was 86 (good).The students passing studying in cycle I was 32 (82,05%)and increased in cycle II became 38 (97,43%). The average of affective aspect in cycle Iwas 73 (less) increased in cycle II that was 86 (good). Science skill process inpsychomotor aspect was 70 (enough) in cycle I and became 86 (good) in cycle II. Thoseresults proved that the implementation ofmodel discovery learning and authenticassessment was able to increase the student science skill process in class X.1AK SMKFarmasi Ikasari Pekanbaru academic year 2015/2016..Key words : Model Discovery Learning, Assessment Authentic, Science Skill Process